The History of the Peloponnesian War - Thucydides, 456? BCE-396 BCE; Crawley, Richard, 1840-1893 (Salt Lake City, UT : Project Gutenberg, 2004)
"The History of the Peloponnesian War" by Thucydides is a historical account written between 431-411 BC. It chronicles the devastating conflict between Sparta's Peloponnesian League and Athens' Delian League. Written by an Athenian general who fought in the war, this unfinished work ends abruptly mid-sentence. Considered one of the earliest scholarly histories, it employs strict chronology and extensive speeches while attempting objectivity. Thucydides attributes events to human choices rather than divine intervention, establishing methods that shaped Western historical writing. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/History_of_the_Peloponnesian_War
Release date is 2004-12-01
Albert Imrie and David Widger
Keywords: Greece -- History -- Peloponnesian War, 431-404 B.C.